Evaluasi Satu Dekade Pembangunan Zona Integritas di Instansi Pemerintah Pusat Indonesia - Zahra Wanisa; Roy Valiant Salomo (Sawala : Jurnal Administrasi Negara, 2023)
Integrity in public institutions is an important thing that needs attention in achieving bureaucratic reform. Indonesia has established a policy of developing integrity zones (ZI) in government agencies to improve the implementation of excellent public services, free of corruption, collusion, and nepotism. This study aims to evaluate the implementation of ZI development in Indonesian Central Government Agencies. The evaluation is carried out to see changes and the impact of policy implementation comprehensively. This study used qualitative methods through in-dept interviews and study documents. The study results concluded that the implementation of ZI Development policies in Indonesian Central Government Agencies had been quite good to regard ZI development as a series of implementations of Indonesian bureaucratic reform. New values have been formed in work units with ZI predicate WBK/WBBM. The Public Service Index for Central Government Agencies increases yearly, above the national index value. However, several obstacles are encountered, including awareness and understanding of the meaning/essence still needs to be optimized, and the number of PANRB Ministry human resources as supervisors and evaluators considering a large number of work units of the Indonesian government agencies.